Maternal anxiety versus depressive disorders: specific relations to infants' crying, feeding and sleeping problems. (22nd October 2015) - Petzoldt, J.; Wittchen, H.‐U.; Einsle, F.; Martini, J.
Abstract: Background: Maternal depression has been associated with excessive infant crying, feeding and sleeping problems, but the specificity of maternal depression, as compared with maternal anxiety remains unclear and manifest disorders prior to pregnancy have been widely neglected. In this prospective longitudinal study, the specific associations of maternal anxiety and depressive disorders prior to, during and after pregnancy and infants' crying, feeding and sleeping problems were investigated in the context of maternal parity. Methods: In the Maternal Anxiety in Relation to Infant Development (MARI) Study, n = 306 primiparous and multiparous women were repeatedly interviewed from early pregnancy until 16 months post partum with the Composite International Diagnostic Interview for Women (CIDI‐V) to assess DSM‐IV anxiety and depressive disorders. Information on excessive infant crying, feeding and sleeping problems was obtained from n = 286 mothers during postpartum period via questionnaire and interview (Baby‐DIPS). Results: Findings from this study revealed syndrome‐specific risk constellations for maternal anxiety and depressive disorders as early as prior to pregnancy: Excessive infant crying (10.1%) was specifically associated with maternal anxiety disorders, especially in infants of younger and lower educated first‐time mothers. Feeding problems (36.4%) were predicted by maternal anxiety (and comorbid depressive) disorders in primiparous mothers and infants with lower birth weight. Infant sleeping problems (12.2%) were related to maternal depressive (and comorbid anxiety) disorders irrespective of maternal parity. Conclusions: Primiparous mothers with anxiety disorders may be more prone to anxious misinterpretations of crying and feeding situations leading to an escalation of mother–infant interactions. The relation between maternal depressive and infant sleeping problems may be better explained by a transmission of unsettled maternal sleep to the fetus during pregnancy or a lack of daily structure and bedtime routine with the infant. Maternal disorders prior to pregnancy require more attention in research and clinical practice.